USING YOUTUBE VIDEOS BY ENGLISH WITH LET’S TALK-FREE ENGLISH LESSONS CHANNEL IN IMPROVING THE EFL STUDENTS’ VOCABULARY MASTERY IN FIRST GRADE OF SMP NEGERI 2 MANGARABOMBANG TAKALAR - Nur Indrawati Nawir; Muh. Tahir; Sultan Baa (Universitas Negeri Makassar, 2022)
This research aims at finding out whether or not using YouTube videos in English with the let’s talk-free English lessons channel in improving the EFL students’ vocabulary mastery in first grade of SMP Negeri 2 Mangarabombang Takalar. This study uses a quantitative method with a pre-experimental research design, where the sample is class VII A, with Twenty-three (23) students, and uses simple random sampling. The instrument used is a test (posttest and pretest) which has the purpose to obtain data for the study. The results of the data analysis showed that by watching YouTube videos students' vocabulary mastery improved. It can be proven by the t-test value was lower than P (0.000 ˂ 0.05) which means (H0) of this research was rejected and (H1) was accepted. in addition, it is concluded that using YouTube video in English with let’s talk-free English lessons channel can develop the vocabulary mastery of the first-grade students of SMP Negeri 2 Mangarabombang Takalar.